Migrant Activism in Contexts of Discrimination: Political Strategies and Competitiveness in the Associative Sphere - Tarullo, Raquel; Renedo Farpón, Cristina; Díez-Garrido, María (PARTECIPAZIONE E CONFLITTO, 2026)
The political participation of migrants reveals a fundamental tension between their positioning as objects of welfare policies and their potential as active political subjects. Based on this premise, the present study examines the forms of activism promoted by Latin American migrant social organisations in Spain, within a context marked by the increasing visibility and diversification of migrant activism. A mixed-methods approach was applied, combining quantitative and discourse analysis of the official accounts of diaspora associations with semi-structured interviews conducted with representatives of these movements. The findings show that, while associations mobilise repertoires of action aligned with immigrant politics, their involvement in traditional political arenas remains limited, shaped by dependence on public funding and organisational precarity. Active mobilisation is concentrated in digital campaigns against racism and xenophobia. Moreover, the persistence of colonial logics is evident through institutional mechanisms of control that curtail the autonomy of these organisations. At the same time, the communicative practices developed by these associations can be understood as forms of communicative resilience, especially in relation to the networks of solidarity they establish and their efforts to sustain political and cultural presence despite structural constraints. The study concludes that, even when agency is exercised, migrant associations continue to face structural barriers that hinder their full recognition as political actors, thereby reproducing symbolic forms of exclusion in the host society.